1979
DOI: 10.1111/j.1440-1754.1979.tb01241.x
|View full text |Cite
|
Sign up to set email alerts
|

Childproof Safety Barriers An ergonomic study to reduce child trauma due to environmental hazards

Abstract: Nixon, J. W., Pearn, J. H. and Petrie, G. M. (1979). Aust. Paediatr. J., 15, 260–262 Childproof safety barriers. An ergonomic study to reduce child trauma due to environmental hazards. Trauma is the biggest killer of young children in Australia. An ergonomic study has been undertaken to test the ability of 500 Australian children to pass safety fences of various heights. Eighty per cent of 2 year olds, the modal age for child drowning, cannot climb a 60 cm (2 ft) fence. Twenty percent of 3 year olds can climb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The height and design of the fence remains a challenge, particularly to define what is the effective height to prevent children from climbing into the pool area, as well as ensuring that the fence is not climbable. The first works by Nixon et al (1979) found that a 1.4 m fence can be climbed by 0% of threeyear-olds, a 1.2 m fence by 18%, and a 90 cm fence by 55%. With that, it was instituted that fences over 1.2 m, without transverse scalable stakes and taking care not to leave close to objects such as pitchers that could be used to overcome the fence, are effective in preventing these falls.45 Another important The measure implemented was the recognition of the lifeguard profession and, despite being a state and municipal determination, there is a recommendation for the presence of at least two of these professionals for every 300m² of water surface during hours of use of public and collective swimming pools, understood as those used in clubs, condominiums, schools, associations, hotels and public and private parks.…”
Section: Resultsmentioning
confidence: 99%
“…The height and design of the fence remains a challenge, particularly to define what is the effective height to prevent children from climbing into the pool area, as well as ensuring that the fence is not climbable. The first works by Nixon et al (1979) found that a 1.4 m fence can be climbed by 0% of threeyear-olds, a 1.2 m fence by 18%, and a 90 cm fence by 55%. With that, it was instituted that fences over 1.2 m, without transverse scalable stakes and taking care not to leave close to objects such as pitchers that could be used to overcome the fence, are effective in preventing these falls.45 Another important The measure implemented was the recognition of the lifeguard profession and, despite being a state and municipal determination, there is a recommendation for the presence of at least two of these professionals for every 300m² of water surface during hours of use of public and collective swimming pools, understood as those used in clubs, condominiums, schools, associations, hotels and public and private parks.…”
Section: Resultsmentioning
confidence: 99%
“…While the barrier is seen as a more effective measure within the Hierarchy of Controls, there is however the ongoing challenge faced by parents in ensuring that young children in their care are kept safe. To help parents understand what is required and to remind them of the strategies available, continuing education will be required to: ensure they supervise their children when in, on, or near water; they check that the pool fence is in good working order; and they create an environment where the child is not allowed to climb the fence [ 15 ]. From this survey, there were differing groups where this is going to be more challenging, such as homeowners, people with higher household incomes, people age 45–54, those separated or divorced, and those with a pool at home.…”
Section: Discussionmentioning
confidence: 99%
“…Fence height and design continues to be a challenge, particularly in defining what an effective height is to stop children from climbing into the pool area, as well as ensuring that the fence is non-climbable. Early work by Nixon et al (1979) found that a 1.4 m fence was able to be climbed by 0% of three-year-old children, a 1.2 m fence by 18%, and a 90 cm fence by 55% [ 15 ]. The preferred height was 1.4 m, however, a compromise was reached by the Australia Standards committee that 1.2 m would be used.…”
Section: Introductionmentioning
confidence: 99%